2009
DOI: 10.1073/pnas.0812183106
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate increases IL-1 receptor antagonist but decreases T cell-induced IL-1β in human monocytes and multiple sclerosis

Abstract: Mechanisms of action as well as cellular targets of glatiramer acetate (GA) in multiple sclerosis (MS) are still not entirely understood. IL-1␤ is present in CNS-infiltrating macrophages and microglial cells and is an important mediator of inflammation in experimental autoimmune encephalitis (EAE), the MS animal model. A natural inhibitor of IL-1␤, the secreted form of IL-1 receptor antagonist (sIL-1Ra) improves EAE disease course. In this study we examined the effects of GA on the IL-1 system. In vivo, GA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 41 publications
11
115
0
1
Order By: Relevance
“…We previously demonstrated that GA increases the circulating levels of sIL-1Ra in GA-treated MS patients and EAE mice (29). This observation corroborates the triggering of sIL-1Ra production by GA in isolated blood monocytes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We previously demonstrated that GA increases the circulating levels of sIL-1Ra in GA-treated MS patients and EAE mice (29). This observation corroborates the triggering of sIL-1Ra production by GA in isolated blood monocytes.…”
Section: Discussionsupporting
confidence: 79%
“…PI3Ks and extracellular signal-regulated kinase-1/2 (ERK1/2) have been shown to contribute to the induction of sIL-1Ra in monocytes. To assess whether GA was able to turn on PI3K/Akt and MAPK pathways, monocytes were activated by an optimal concentration of GA (25 μg/mL) that was previously determined (29). GA induced the phosphorylation of Akt and ERK1/2, i.e., downstream elements of PI3Ks and MEK1/2, both kinases being coordinately phosphorylated, reaching a maximum at 2 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For active immunization, 8-week-old mice were immunized with MOG 35-55 as described [56]. Briefly, female B6 mice deficient in TLR7 and WT were immunized with 100 μg MOG in CFA containing MT, subcutaneously on the right flank (100 μL/animal) on day 0.…”
Section: Mice and Induction Of Eaementioning
confidence: 99%